2020
DOI: 10.3390/jcm9082664
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Adverse Cardiovascular Events in Cancer Patients Treated with Bevacizumab

Abstract: Background: Bevacizumab, a vascular endothelial growth factor (VEGF) monoclonal antibody commonly used for the treatment of various cancers, is often associated with adverse cardiovascular effects such as hypertension, cardiac and cerebral ischemia, thrombosis, and bleeding events. Factors associated with increased risks of adverse cardiovascular effects with bevacizumab have not been intensively studied. In this study, we determined factors associated with hospital admissions due to cardiovascular complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Remarkably, the incidence of CV events was lower in subsequent postmarketing analyses, which included subjects with a better CV risk profile as compared with those enrolled in the PACE trial, lending support to the consideration that there is an interaction between CV risk factors and the CV toxicity of TKI 61 . Other recent clinical reports have confirmed the clinical relevance of inhibition of VEGF and TK, and the association of the CV profile with the risk of adverse CV events 62–64 …”
Section: Cardio‐oncology Knowledge To Address the Possible Cardiovascular Risk Of Nintedanib Therapymentioning
confidence: 76%
“…Remarkably, the incidence of CV events was lower in subsequent postmarketing analyses, which included subjects with a better CV risk profile as compared with those enrolled in the PACE trial, lending support to the consideration that there is an interaction between CV risk factors and the CV toxicity of TKI 61 . Other recent clinical reports have confirmed the clinical relevance of inhibition of VEGF and TK, and the association of the CV profile with the risk of adverse CV events 62–64 …”
Section: Cardio‐oncology Knowledge To Address the Possible Cardiovascular Risk Of Nintedanib Therapymentioning
confidence: 76%
“…In these patients, the number of patients who develop acute myocardial infarction, coronary artery disease, and thromboembolic event are 14.81%, 19.23%, and 17.86%, respectively (26). Additionally, a retrospective cohort study reported that in cancer patients (multiple types) treated with bevacizumab, 28 out of 230 patients were re-treated in hospital due to major cardiovascular-related events (27).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in ocular vascular degenerative disorders, several anti-VEGF therapies have been approved for clinical use but show limited improvements in many clinical trials (246). While some benefits have been observed in several studies for the various diseases and conditions discussed here, the side effects associated with anti-VEGF or anti-VEGFR-2 therapies can be severe and include heightened risk of arterial thromboembolic events, hypothyroidism, wound healing complications, GI perforations, neutropenia and hematological effects and increased risks for other cardiac adverse events (245,(247)(248)(249). If future treatments combine anti-VEGFR-2 and anti-mechanotransductive elements, additional side effects could be expected if the latter pathways are ubiquitous in healthy and diseased tissues.…”
Section: Anti-vegf Treatments Side Effects and Efficacymentioning
confidence: 99%